Neurotized Distally Based Sural Flap for Heel Reconstruction - Mendieta, Mauricio J.; Roblero, Carlos; Vega, Juan C. (Journal of Reconstructive Microsurgery, 2013)
The use of local flaps for the reconstruction of leg has lost their popularity with the more often performed flaps on the basis of perforators and microsurgical technique. Like the head and neck reconstruction, in the lower extremity there are limited units of tissue to base the flaps because of the lack of vascularity and arc of mobilization. The distally based sural flap represents an ideal flap for the reconstruction of heel, and with the inclusion of the sural nerve, we can neurotize the flap to give the stability of a weight-bearing area and provide the necessary sensibility to avoid ulcerations of the reconstructed heel. We present a case of a 32-year-old woman with a traumatic loss of the tissue covering the heel, with a diagnosis of a pseudoepithelial hyperplasia treated in previous occasions with skin grafts that led to chronic ulcerations. A distally based sural flap was planned for a definitive coverage, planning a perineural neurorrhaphy, to the intermediate dorsal cutaneous branch of the superficial peroneal nerve to give sensibility to the flap.
Keywords: sural flap; neurocutaneous flap; heel reconstruction